2021
DOI: 10.1080/21645515.2020.1871571
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the coronavirus disease 2019 epidemic and a free influenza vaccine strategy on the willingness of residents to receive influenza vaccines in Shanghai, China

Abstract: The influenza vaccine is not included in China’s national immunization program. Here, we assessed influenza vaccine coverage among Shanghai residents and estimated the impacts of the coronavirus disease 2019 (COVID-19) epidemic and a hypothetical free vaccine strategy on the willingness of participants to receive influenza vaccines. The coverage of influenza vaccines among Shanghai residents from 2015 to 2019 was 1.4% (range: 1%–2.4%). A total of 792 adult participants (aged 19–59 years) along with 821 childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…Third, the vaccination coverage of respondent parents in our study was unsure, which may generate interaction with parents’ preferences toward different attributes. Finally, the COVID-19 pandemic improved the individuals’ willingness to receive influenza vaccination [ 42 , 43 ]; however, its impact could not be explored in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the vaccination coverage of respondent parents in our study was unsure, which may generate interaction with parents’ preferences toward different attributes. Finally, the COVID-19 pandemic improved the individuals’ willingness to receive influenza vaccination [ 42 , 43 ]; however, its impact could not be explored in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis including 126 studies showed that influenza vaccine coverage is less than 30% among children in mainland China [ 6 ]. The estimated five-year average influenza vaccination coverage among children is 5.5% in Shanghai, China [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on cognitive appraisal theory, people may have different risk perceptions regarding potential or actual consequences and the uncontrollability of the COVID-19 pandemic [ 16 , 20 ]. Additionally, because there are similar initial symptoms between influenza and COVID-19, interest in a safe and effective influenza vaccine may increase [ 7 , 21 ]. Compared with the pre-pandemic period, willingness to receive influenza vaccines for children increased significantly following the COVID-19 epidemic (78.4% vs. 64.8%) in Shanghai, China [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the public's intention to vaccinate against seasonal influenza and pneumonia during the COVID-19 pandemic [20][21][22][23]. Some of these studies have shown that the COVID-19 pandemic might positively impact the public's demand for seasonal influenza and pneumonia vaccinations [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the public's intention to vaccinate against seasonal influenza and pneumonia during the COVID-19 pandemic [20][21][22][23]. Some of these studies have shown that the COVID-19 pandemic might positively impact the public's demand for seasonal influenza and pneumonia vaccinations [20][21][22]. Possible reasons for this are that influenza, pneumonia, and COVID-19 can present with similar symptoms [24,25], and beyond that, they share the same risk groups, proving detrimental to older persons and persons with chronic diseases [26,27].…”
Section: Introductionmentioning
confidence: 99%